EVALUASI SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PENJUALAN PADA BISNIS KUINER (STUDI KASUS PADA OUTLET MIE SAKERA CABANG DANAU TOBA) - Maulida, Vika Intan; Halim, Moh.; Aspirandi, Rendi Mirwan (Relawan Jurnal Indonesia, 2023)
An accounting information system is a system that provides accounting and financial information along with other information obtained from routine accounting transaction processes. The information produced by the accounting information system includes, among other things, information regarding sales orders, cash receipts, purchase orders, payments and payroll. Based on analyzing the system running at the Mie Sakera Caban Lake Toba Jember business and looking at the existing problems, it is necessary to create a Web-based or computer-based Product Sales Information System, namely a system which helps the operational sales process in a systematic manner starting from inventory data and sales data which has been carried out automatically by the user so as to produce output in the form of information that is useful for the owner. This system must be designed so that it can access data easily, in a comprehensive system starting from inventory data, sales data as well as simplifying the product sales process with extensive promotions and an effective and efficient reporting process by integrating data through a database.